A synchronization technique for single-phase grid applications - Issam A. Smadi; Saher A. Albatran; Taher Q. Ababneh (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
The utility grid disturbances like dc offset and harmonic components can severely affect the estimated variables from the phase-locked loop (PLL), resulting in poor performance of the system relying on it. Therefore, there is an emerging need for well-designed PLL algorithms ensuring robust response against different operating conditions. This paper proposes a simple single-phase PLL algorithm with inherent dc offset and specific harmonic orders rejection capability. Utilizing adaptive time-delay fictitious signal generation. A full mathematical model of the proposed PLL has been provided. The proposed PLL is compared with other filter-based single-phase PLLs, to validate its simplicity and excellent performance.